The Legal Force of Electronic Signatures in Online Mortgage Registration - Zainuddin Zainuddin; Rahmat Ramadhani (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The legal force of electronic signatures in online mortgage registration activities is an important subject to study. Because basically the legal problems of electronic mortgage registration are also related to the validity of electronic signatures of persons who are not present before an LDO. Another issue that is important to study regarding the electronic signature in question is regarding the time limit of 7 (seven) days to register the Deed of Grant of Mortgage to the Land Registry Office. If it exceeds that time limit, the deed in question becomes null and void and it also causes sanctions against LDO. The research method used is normative juridical legal research that focused on two problems, namely; How is the legal force of electronic signatures in online mortgage registration? What are the legal problems of online mortgage registration? The results of the research showed that the Regulation of the Minister of Agrarian and Spatial Planning/the Head of National Land Agency Number 9 Year 2019 concerning Electronically Integrated Mortgage Services substantially has a tendency to contradict some of the regulations above it. Therefore, there is no detailed data protection relating to the securities registered in the electronic mortgage registration. Ignoring the time limit of 7(seven) days will also result in administrative sanctions up to the dismissal of the LDO who neglect their duties.